Decolonial thinking: final thoughts - Mignolo, Walter D. (2016)
The author defines and characterizes de-colonial thought while at the same time posing elements of differentiation of this thought with other dissident and critical ways of thinking generated by modernity. Finally, Mignolo indicates how the university should contribute to the democratic processes in two ways: producing de-colonized thought and building relations between this thought and the de-colonized thought produced outside the university.